The changing face of the paediatric microlaryngobronchoscopy (MLB): A two year prospective study. Issue 7 (July 2015) - Cadd, Brandon; Yalamanchili, Seema; Virk, Jagdeep Singh; Bajaj, Yogesh
Abstract Background Changes in the management and survival of paediatric patients with airway complaints combined with improving survival rates of premature babies have resulted in a different patient population for the paediatric airway surgeon than that previously described in the literature. Objectives To examine the presentation, diagnosis, clinical course and outcomes for patients undergoing microlaryngobronchoscopy (MLB). Study design: 2 year prospective longitudinal study. Study population: 210 microlaryngobronchoscopy examinations were performed on a total of 102 patients. Mean age at initial examination was 29.4 months with a male preponderance (68%). Results 72 (71%) patients had other documented medical co-morbidities with 30 children having no previous medical history. Of the 102 patients the primary diagnoses were: Subglottic Stenosis (29.4%), Laryngomalacia (20.6%), Laryngeal Cleft (16.7%), Normal Anatomy (11.8%) and Vocal Cord pathology (5.9%). The average rate of diagnoses per patient for the whole cohort was 1.57. Of those patients with a diagnosis on examination, 40 had a solitary diagnosis whilst 50 patients (55.5%) were found to have multiple diagnoses, equating to 2.35 diagnoses per patient. Children with a history of prematurity accounted for 18.6% of our cohort with a 100% rate of laryngo-tracheal pathology on examination and an average number of diagnoses per child of 2.21. Conclusion Our cohort illustrates the varied population served by today's paediatric airway surgeon alongside common diagnoses and co-pathologies affecting our patients.